653 Dasatinib as a rapid pharmacological ON/OFF switch for T cell bispecific antibody-induced T cell activation and cytokine release. (10th December 2020) - Leclercq, Gabrielle; Haegel, Helene; Schneider, Anneliese; Berger, Estelle Marrer; Walz, Antje; Boetsch, Christophe; Pulko, Vesna; Ferlini, Cristiano; Klein, Christian
Abstract : Background: T cell bispecific antibodies (TCBs) are extremely potent T cell engagers, harboring a 2+1 format with one binder to the CD3ε chain and two binders to specific tumor antigens. Crosslinking of CD3 with tumor antigens triggers T cell activation, proliferation and cytokine release, leading to tumor cell killing. 1 2 TCB treatment is sometimes associated with safety liabilities due to on-target on-tumor, on-target off-tumor cytotoxic activity and cytokine release. Patients treated with TCBs may experience a Cytokine Release Syndrome (CRS), characterized by fever, hypotension and respiratory deficiency and associated with the release of pro-inflammatory cytokines such as IL-6, TNF-α, IFN-γ, and IL-1β. 3 Off-tumor toxicity may occur if target antigens are expressed in healthy cells, which may potentially result in tissue damages and compromise the patient's safety. Rapid pharmacological blockade of T cell activation and proliferation is a promising approach to mitigate these life-threatening toxicities. Tyrosine kinases such as SRC, LCK or ZAP70 are involved in downstream signaling pathways after engagement of the T cell receptor and blocking these kinases might serve to abrogate T cell activation when required. Dasatinib was identified as a potent candidate that switches off CAR T cell functionality. 4 5 Methods: Using an in vitro model of target cell killing by human peripheral blood mononuclear cells, we assessed the reversible effects of dasatinib combined with CEA-TCB or HLA-A2-WT1-TCB on T cell activation and proliferation, target cell killing and cytokine release. At assay endpoints, T cell phenotype and target cell killing were measured by flow cytometry and supernatants were analyzed by Luminex to assess cytokine release. To determine the effective dose of dasatinib, the Incucyte system was used to follow kinetics of target cells killing by TCB in the presence of a dose response of dasatinib concentrations. Results: 100 nM dasatinib prevented TCB-mediated target cell killing when added in the system upon restimulation of activated T cells (figure 1 ). Dasatinib concentrations above 50 nM fully switched off target cell killing (figure 2 ) which was restored upon removal of dasatinib. These data confirm that dasatinib act as a potent and reversible on/off switch for activated T cells at pharmacologically relevant doses as they are applied in patients according to the label. 6 Conclusions: Taken together, we provide evidence for the use of dasatinib as a pharmacological on/off switch to mitigate off-tumor toxicities or CRS by T cell engaging therapies. These data are being validated in vivo. References: Bacac M, Fauti T, Sam J, Colombetti S, Weinzierl T, Ouaret D, et al. A novel carcinoembryonic antigen T-Cell Bispecific Antibody [CEA TCB] for the treatment of solid tumors. Clin Cancer Res 2016;22(13):3286–97. Bacac M, Klein C, Umana P. CEA TCB: A novel head-to-tail 2:1 T cell bispecific antibody for treatment of CEA-positive solid tumors. Oncoimmunology 2016;5(8):e1203498. Shimabukuro-Vornhagen A, Gödel P, Subklewe M, Stemmler HJ, Schlößer HA, Schlaak M, et al. Cytokine release syndrome. J Immunother Cancer 2018;6(1):56. Weber EW, Lynn RC, Sotillo E, Lattin J, Xu P, Mackall CL. Pharmacologic control of CAR-T cell function using dasatinib. Blood Advances 2019;3(5):711–7. Mestermann K, Giavridis T, Weber J, Rydzek J, Frenz S, Nerreter T, et al. The tyrosine kinase inhibitor dasatinib acts as a pharmacologic on/off switch for CAR T cells. Science Translational Medicine 2019;11(499):eaau5907. Wang X, Roy A, Hochhaus A, Kantarjian HM, Chen TT, Shah NP. Differential effects of dosing regimen on the safety and efficacy of dasatinib: retrospective exposure-response analysis of a Phase III study. Clinical pharmacology : advances and applications 2013;5 :85–97.